200 Circulating Pro-Endothelin-1 (CT-proET-1) and Pulmonary Morbidity in Newborn Infants. (October 2012) - Wellmann, S; Benzing, J; Stabile, O; Szinnai, G; Morgenthaler, NG; Schulzke, SM; Bührer, C
Abstract : Background and aims: Plasma concentrations of endothelin-1 (ET-1), a potent pulmonary vasoconstrictor with a short serum half-life, can be estimated by measuring its stable by-product, C-terminal pro-Endothelin-1 (CT-proET-1). To investigate the association between CT-proET-1, gestational age, and pulmonary morbidity in newborn infants. Methods: A prospective cross-sectional study at two tertiary university hospitals was conducted. CT-proET-1 concentrations (pmol/L) were determined in plasma samples of 293 newborn infants (gestational age 24–41 weeks) at birth and on day 3 of life with BRAHMS KRYPTOR automated immunoflorescent assay. Results: At birth, CT-proET-1 concentrations were unrelated to birth weight and gestational age. Venous umbilical cord CT-proET-1 concentrations were consistently higher than matched arterial ones (M 148 vs. 134 pmol/L, p<0.001), but both values were closely related (RS =0.745, p<0.001). There was large postnatal increase of CT-proET-1 in infants with pulmonary morbidity. Days of mechanical ventilation, continuous positive airway pressure (CPAP), and oxygen supplementation correlated each with CT-proET-1 level on day 3 (RS 0.566, 0.658, and 0.819, respectively, for all p<0.001). Conclusions: In term and preterm newborn infants, pulmonary compromise is associated with increased concentrations of circulating CT-proET-1.